Kondisi Sosial Ekonomi Keluarga Buruh Perkebunan Karet Di Desa Bangun Sari Kecamatan Lima Puluh Kabupaten Batu Bara - Aidil Safitri (Universitas Muhammadiyah Sumatera Utara, 2022)
Rubber plantation is one of the important sectors for the Indonesian economy. In rubber plantations all work activities can require a lot of labor. In fact, the wages of plantation workers are much higher due to government intervention and the existence of strong trade unions. Apart from cash, the company also provides other facilities such as housing and other health care facilities. The formulation of the problem from this research is How the Socio-Economic Condition of the Rubber Plantation Workers' Family in Bangun Sari Village, Lima Puluh District, Batu Bara Regency. The socio-economic living conditions of the workers will be an indicator of how much wages are earned from the company where the workers work, and through this wage it will be seen how the workers' consumption culture is with the various facilities provided by the company. In this condition, the wages earned by the workers will be a benchmark for the extent to which the workers can still live properly and the socio-economic conditions of the workers can be fulfilled. This research uses descriptive qualitative research method with an inductive approach which describes the problem based on the existing facts. The results of this study are the education level of the family of plantation workers is relatively low, while the socioeconomic conditions of the families of rubber plantation workers in Bangun Sari Village, Lima Puluh District, Batu Bara Regency already have a fairly decent life where their average income is sufficient to meet their needs and they have owns a private house with permanent conditions as well as several other assets. The conclusion is that with this low level of education, they only have jobs as plantation workers.